Christianity and Social Change in Contemporary Africa: Volume One - Carpenter, Joel A.; Nyamnjoh, Francis B., 1961- (Book collections on Project MUSE., 2020)
This volume brings together seven empirically grounded contributions by African social scientists of different disciplinary backgrounds. The authors explore the social impact of religious innovation and competition in present day Africa. They represent a selection from an interdisciplinary initiative that made 23 research grants for theologians and social scientists to study Christianity and social change in contemporary Africa. These contributions focus on a variety of dynamics in contemporary African religion (mostly Christianity), including gender, health and healing, social media, entrepreneurship, and inter-religious borrowing and accommodation. The volume seeks to enhance understanding of religion's vital presence and power in contemporary Africa. It reveals problems as well as possibilities, notably some ethical concerns and psychological maladies that arise in some of these new movements, notably neo-Pentecostal and militant fundamentalist groups. Yet the contributions do not fixate on African problems and victimization. Instead, they explore sources of African creativity, resiliency and agency. The book calls on scholars of religion and religiosity in Africa to invest new conceptual and methodological energy in understanding what it means to be actively religious in Africa today.